Development of Urban Waste Recycling Industry from the Perspective of Ecology - Qian Luo (International Journal of Antennas and Propagation)
Urban garbage has become an important field affecting the healthy development of urban ecology, and urban ecological environment protection has naturally become a crucial part in the process of modern urban development. Deepening the relevant concepts of ecological and environmental protection also makes modern cities pay attention to the recycling and utilization of waste resources. This work is combined with the development status of urban waste recycling industry. Taking urban construction waste and domestic waste as examples, this paper focuses on the operation model and development path of urban waste recycling industry. For example, in the aspect of domestic waste treatment, the resource industrialization path of incineration fly ash is proposed, focusing on the water washing and dechlorination of incineration fly ash, the production of unburned ceramsite from water washed fly ash, and the separation and recovery of inorganic salts in fly ash water washing solution. The results show that the recoveries of NaCl, KCl, and CaCl2 are 96.21%, 95.85%, and 94.72%. Through the analysis of social, environmental, and economic benefits, the government, scientific research institutions, and enterprises are encouraged to make joint efforts to develop the construction waste recycling industry, so as to fundamentally solve the current situation of “mountains of garbage and cities surrounded by garbage” in China.